Web-Based Heart Disease Diagnosis System With Forward Chaining Method (Case Study Of Ibnu Sina Islamic Hospital) - Refni Wahyuni; Yuda Irawan (Journal of Applied Engineering and Technological Science (JAETS), 2019)
Expert systems are computer-based applications that are used to solve problems thought by experts. The benefits of expert systems are to find solutions to problems that occur in various fields including medicine and medical. The problem that often occurs is the problem of public knowledge of the initial problems of heart disease and the lack of public attention to heart health. From this problem, the writer wants to raise the title "Expert System of Web-Based Heart Disease Diagnosis with Forward Chaining Method (Case Study of Ibnu Sina Islamic Hospital)". The purpose of this system is so that people can understand, understand the facts of heart disease. The method used in making this system is forward chaining because this method is a punishment starting from the fact that it contains sentences that are received. The output of this system is a diagnosis of heart disease, as well as providing recommendations for how to treat the disease.